Pengaruh Waktu Perendaman terhadap Daya Serap Air dan Drop Test pada Paving Block Plastik-Pasir - N P G Suardana; Rizki Andika Putra; C I P K Kencanawati (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2020)
Garbage is a problem that exists in every province in Indonesia including th e Province of Bali. Most of it comes from plastic waste, which causes many problems for which the solution to handle them is still unsolved. Researchers used an alternative by means of the chopping process and the process of liquefying plastic waste which is used as a paving block. The materials used include sand with a grain size of 2 -3 mm as reinforcement and plastic waste as a cement substitute binder. Plastic and sand are mixed in a furnace heatedat 200 °C. The testing process for plastic-sand paving blocks uses several standards as a reference, such as SNI-03-0691 1996 for the quality requirements of concrete bricks and ASTM D440 -86 for the Standard Test Method of Drop Shatter Test for Coal. This research was conducted to determine the effect of water immersion time on the physical and mechanical characteristics of plastic-sand paving blocks. The immersion was carried out consecutively for 15, 30, 45, and 60 days, then a drop test was carried out from a height of 3m for each immersion time. The results showed that the immersion time affected the percentage value of absorption and damage to plastic-sand paving blocks. The highest value of absorption and damage was obtained in paving blocks with a ratio of 1: 4 and a long soaking time of 60 days.